(untitled) (Journal of Medicine, 2014)
Background: Heart failure is a complex clinical syndrome that arises secondary to abnormalities of cardiac structure and/or function (inherited or acquired) that impair the ability of the left ventricle to fill or eject blood. The worldwide prevalence and incidence rates of heart failure (HF) are approaching epidemic proportions, as evidenced by the relentless increase in the number of HF hospitalizations, the growing number of HF-attributable deaths, and the spiraling costs associated with the care of HF patients. Worldwide, HF affects nearly 23 million people. In the United States, HF affects approximately 4.7 million persons (1.5 to 2 percent of the total population), with approximately 550,000 incident cases of HF diagnosed annually. Heart failure patients have various presentations and different etiologies. So, this study aimed to see the different clinical presentations of hospitalized heart failure patients. Methods: This study was done to see Clinical Presentation of Heart Failure Patients admitted in National Institute of Cardiovascular Diseases, Dhaka. Total 2112 patients were enrolled for this study during the period of August 2006 to July 2011. Results: Most of the patients (65%) were of 51-70 years age group. 75% (1584) patients were male. 98% patients presented with SOB, 95% patients had basal crepitation, 74% had orthopnoea, 59% had Paroxysmal Nocturnal Dyspoea (PND), 40% had leg edema and 25% had raised JVP. Average heart rate was 85 beats/min, average systolic B.P. was 118 mm Hg and average diastolic B.P. was 73 mm Hg. 45% population had hypertension, 29% patients had diabetes and 27% had concomitant respiratory illness. Average EF was 38%. Ischemic Cardiomyopathy was the commonest (39%) cause of heart failure, acute coronary syndrome was the second leading (29%) cause and valvular heart disease is the third common cause. Conclusion: Most of the heart failure patients are elderly age group. Most of the patients presented with shortness of breath and bilateral basal creps. Most patients had co-morbid other illness that influences the natural course of heart failure patients. Most common causes are ischemic cardiomyopathy, a sequel of ischemic insult of the heart. So, patients of acute or chronic ischemic heart diseases should be treated and follow up with care, considering their socioeconomic condition also. DOI: http://dx.doi.org/10.3329/jom.v15i1.19854 J Medicine 2014; 15: 18-22